Unveiling asexual reproductive traits in black corals: polyp bail-out in Antipathella subpinnata - Martina Coppari; Lara Fumarola; Lorenzo Bramanti; Pascal Romans; Rémi Pillot; Giorgio Bavestrello; Marzia Bo (Coral Reefs, 2020)
Cnidarians are known to undergo reverse development as a survival mechanism against adverse environmental conditions. Polyp bail-out consists in the polyps’ detachment from the mother colony due to stressful conditions, followed by a complete tissue and cells rearrangement and in some cases in a regression into a simple, ciliated form. Here we describe a massive polyp bail-out event occurred in the mesophotic black coral Antipathella subpinnata in reared conditions. This is the first report of a bail-out event in this species providing new insights into the life cycle and ecology of black corals.